Dissecting the pathways of doom – application of spectroscopy in the study of cell death and survival - Godlewski, Michał M.; Górka, Magdalena; Gajkowska, Barbara; Wojewódzka, Urszula (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Biological studies rely on measurements performed on large populations, which allow the statistic evaluation of gathered data. On the other hand, the need to precisely localize observed processes and the facts occurring in the microscale results in the need of high resolution qualitative imaging. These two approaches are complementary and without anyone of them no valuable experimental data can be gathered from studies of fluorescent dyes. Both approaches are based on common origin of laser-induced fluorescence, but due to the method of analysis they split into the quantitative (laser scanning cytometry) and qualitative (confocal microscopy) fields of research.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 257-270
Keywords: optyka; spectroscopy; laser scanning cytometry; confocal microscopy; programmed cell death